2011
DOI: 10.1002/cncr.26283
|View full text |Cite
|
Sign up to set email alerts
|

Medullary thyroid microcarcinoma

Abstract: BACKGROUND: Medullary thyroid microcarcinomas (microMTCs) are medullary thyroid carcinomas (MTCs) that measure 1 cm in size for which there is a paucity of data on incidence, characteristics, and clinical significance. METHODS: Patients who had a diagnosis of microMTC were abstracted from the Surveillance, Epidemiology, and End Results database (1988)(1989)(1990)(1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007). The data were analyzed using chi-square tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 73 publications
3
29
1
Order By: Relevance
“…The variance in cure rates may be due to differences in the chronological periods and the ratio of familial disease. Death in microMTC patients has been reported in older studies where the 10-year survival was 96% for localised tumours and 87% for regional tumours (4,19,24). In microMTC patients with positive lymph nodes at diagnosis, undetectable post-operative calcitonin was found in 28.6% compared with 76.8% in those without positive lymph nodes at diagnosis, roughly agreeing with the findings of Scollo et al (15) (32 vs 95%).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The variance in cure rates may be due to differences in the chronological periods and the ratio of familial disease. Death in microMTC patients has been reported in older studies where the 10-year survival was 96% for localised tumours and 87% for regional tumours (4,19,24). In microMTC patients with positive lymph nodes at diagnosis, undetectable post-operative calcitonin was found in 28.6% compared with 76.8% in those without positive lymph nodes at diagnosis, roughly agreeing with the findings of Scollo et al (15) (32 vs 95%).…”
Section: Discussionsupporting
confidence: 88%
“…Hamy et al only observed lymph node involvement; thus, older studies have questioned the extent of surgical treatment needed (7,11,12). However, two recent studies have reported that even small tumours may present with more advanced disease (4,13). Finally, in patients with a hereditary MTC, who frequently have small tumours due to earlier diagnosis, the clinical course and prognosis are better (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If we could divide these negative calcitonin MTC into two categories, one were cancer cells show diffuse staining for calcitonin and another with weak and focal immunoreactivity, we could say that in the first category MTC maintain its ability to produce calcitonin but lose its ability to secrete it, whereas in the second category cancer cells cannot produce calcitonin. In regards to the first type of negative calcitonin MTC, one could hypothesize that there might be a defect in the secretory mechanism, or that the tumor preferential secrete precursor peptides and aberrant forms of calcitonin instead of the mature molecule [6], or that a mutation in the calcitonin/CGRP gene is responsible for the normal or reduced serum calcitonin [4]. When it comes to the second category, we already know that in progressive disease calcitonin levels may decrease due to dedifferentiation [9,15], we could consider that tumor cells with weak calcitonin expression indicate a loss of function and there for dedifferentiation and more aggressive nature [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…In fact it is the second most aggressive thyroid cancer after anaplastic carcinoma [4], with a mortality rate that ranges between 13, 4 -38% [2][3][4][5]. Its poor prognosis relies not only on its aggressive nature but also on its limited response to chemotherapy and radiation [6]. Currently the only possible mean of care for MTC is surgical excision [7].…”
Section: Introductionmentioning
confidence: 99%